Evaluating Diversity Metrics: A Critique of the Equity Index Method - Kenneth D. Royal; Keven Flammer (The Evaluation Center at Western Michigan University, 2015)
Background: Evaluating diversity, inclusivity, and equity remains both a prevalent topic in education and a difficult challenge for most evaluators. Traditional metrics used to evaluate these constructs include questionnaires, focus groups, and anonymous comment solicitations. While each of these approaches offer value, they also possess a number of limitations (e.g., self-reported nature, holistic perspective, social desirability bias, varying degrees of respondent sensitivity, representative responses, etc.). Researchers at the University of Southern California have successfully utilized the Equity Index Method (EIM) as a potential approach for measuring diversity and reporting diversity-related outcomes.   Purpose: Provide a critique of the EIM and discusses how the EIM could be improved and extended to other evaluation contexts and settings.   Setting: Not Applicable.   Intervention: Not Applicable.   Research Design: Not Applicable.   Data Collection and Analysis: Not Applicable.   Findings: Despite the potential for problems with interpretations based on small samples and subgroups and some concerns about semantics involving the term "equity", we believe the EIM possesses a number of strengths that many evaluators will find useful. We encourage other evaluators to consider this method and explore its utility in a variety of contexts.   Keywords: equity; equity index method; applications.